2021
DOI: 10.1111/vop.12878
|View full text |Cite
|
Sign up to set email alerts
|

Presumed neuroprotective therapies prescribed by veterinary ophthalmologists for canine degenerative retinal and optic nerve diseases

Abstract: Objective: To investigate veterinary ophthalmologists' use of presumed neuroprotective therapies for degenerative retinal and optic nerve diseases in dogs.Procedures: An online survey was sent to 663 board-certified veterinary ophthalmologists who were Diplomates of the American College of Veterinary Ophthalmologists (ACVO), Asian College of Veterinary Ophthalmologists (AiCVO), Latin American College of Veterinary Ophthalmologists (Colegio Latinoamericano de Oftalmólogos Veterinarios, CLOVE), or European Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Therefore, there is no current treatment for these conditions. While some advocate the use of nutraceuticals and presumed neuroprotective therapies the practice is not supported by strong research evidence ( 10 ). Furthermore, as demonstrated in people, supplementation with certain vitamins may have adverse effects on specific retinal diseases and therefore caution is advised when advocating for oral supplements ( 11 ).…”
Section: Degenerativementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is no current treatment for these conditions. While some advocate the use of nutraceuticals and presumed neuroprotective therapies the practice is not supported by strong research evidence ( 10 ). Furthermore, as demonstrated in people, supplementation with certain vitamins may have adverse effects on specific retinal diseases and therefore caution is advised when advocating for oral supplements ( 11 ).…”
Section: Degenerativementioning
confidence: 99%
“…The differentiation between glaucoma, trauma or feline metastatic neoplasm is usually straightforward and the diagnosis will guide the recommended treatment plan. While ischemic damage to the retina will often cause severe and irreversible visual deficits, there has been increased interest in the use of neuroprotective agents to spare retinal ganglion cell function ( 10 ).…”
Section: Ischemicmentioning
confidence: 99%
“…For instance, the flavonoid myricetin was shown to lower inflammatory cytokines in the aqueous humor and trabecular meshwork [ 79 ], while omega-3 fatty acid supplementation reduced pro-inflammatory cytokines in tears and improved dry eye symptoms in human patients with glaucoma [ 80 , 81 ]. In veterinary medicine, two recent surveys showed that nutraceutical use is relatively common for glaucomatous dogs [ 7 , 82 ]; however, well-designed prospective studies are desperately needed as today’s evidence is still uncertain and inconclusive [ 83 ].…”
Section: Anti-inflammatory Therapy For Eyes Predisposed or Affected B...mentioning
confidence: 99%
“…Oral medication protocol included gabapentin (10 mg/kg PO q12-8 h; Camber Pharmaceuticals Inc.), prednisone (0.5 mg/kg PO q48 h; West-ward Pharmaceuticals Corp.), methazolamide (2 mg/kg PO q12 h; Ani Pharmaceuticals Inc.), and Ocu-GLO® as a neuroprotective antioxidant supplement. 3 Despite aggressive medical therapy, the patient developed glaucoma in the contralateral eye (OD) 14-days post-phacoemulsification with IOPs of 80 and 18 mmHg OD and OS, respectively. The owner elected to proceed with goniovalve placement OD and the same surgical technique was performed 14-days post-phacoemulsification.…”
Section: Initial Ophthalmic Examinationmentioning
confidence: 99%
“…Topical medication protocol in both eyes included latanoprost 0.005% q8 h (Sandoz Inc.), dorzolamide hydrochloride 2%/timolol maleate 0.5% q6 h (Bausch & Lomb), demecarium bromide 0.125% (Wedgewood Pharmacy), prednisolone acetate 1% q12 h (Pacific Pharmaceuticals USA Inc.), neomycin‐polymyxin B‐sulfate bacitracin zinc q12 h (Bausch & Lomb). Oral medication protocol included gabapentin (10 mg/kg PO q12‐8 h; Camber Pharmaceuticals Inc.), prednisone (0.5 mg/kg PO q48 h; West‐ward Pharmaceuticals Corp.), methazolamide (2 mg/kg PO q12 h; Ani Pharmaceuticals Inc.), and Ocu‐GLO® as a neuroprotective antioxidant supplement 3 . Despite aggressive medical therapy, the patient developed glaucoma in the contralateral eye (OD) 14‐days post‐phacoemulsification with IOPs of 80 and 18 mmHg OD and OS, respectively.…”
Section: Case Reportmentioning
confidence: 99%